Cross-reactivities and cross-neutralization of different envelope glycoproteins E2 antibodies against different genotypes of classical swine fever virus - Chen, Wei-Tao; Liu, Hsin-Meng; Chang, Chia-Yi; Deng, Ming-Chung; Huang, Yu-Liang; Chang, Yen-Chen; Chang, Hui-Wen (Frontiers in Veterinary Science, 2023)
Classical swine fever (CSF) is a highly contagious swine disease caused by the classical swine fever virus (CSFV), wreaking havoc on global swine production. The virus is divided into three genotypes, each comprising 4–7 sub-genotypes. The major envelope glycoprotein E2 of CSFV plays an essential role in cell attachment, eliciting immune responses, and vaccine development. In this study, to study the cross-reaction and cross-neutralizing activities of antibodies against different genotypes (G) of E2 glycoproteins, ectodomains of G1.1, G2.1, G2.1d, and G3.4 CSFV E2 glycoproteins from a mammalian cell expression system were generated. The cross-reactivities of a panel of immunofluorescence assay-characterized serum derived from pigs with/without a commercial live attenuated G1.1 vaccination against different genotypes of E2 glycoproteins were detected by ELISA. Our result showed that serum against the LPCV cross-reacted with all genotypes of E2 glycoproteins. To evaluate cross-neutralizing activities, hyperimmune serum from different CSFV E2 glycoprotein-immunized mice was also generated. The result showed that mice anti-E2 hyperimmune serum exhibited better neutralizing abilities against homologous CSFV than heterogeneous viruses. In conclusion, the results provide information on the cross-reactivity of antibodies against different genogroups of CSFV E2 glycoproteins and suggest the importance of developing multi-covalent subunit vaccines for the complete protection of CSF.